Wegener’s Granulomatosis- A Case Report - Rahman, ASMM; Hoque, A; Haque, Z; Alam, ABMS (TAJ: Journal of Teachers Association, 2009)
Wegener's granulomatosis (WG) is an uncommon condition characterized by necrotizing granulomatosis of the upper and lower respirator y tract and glomerulonephritis. We describe a case of a 23-year-old man with symptoms of frequent nasal discharge with bleeding and occasional cough with blood. In this report, we wanted to emphasize that Wegener's granulomatosis, although rare, should be considered in recurrent epitaxis. TAJ 2009; 22(1): 261-263